Pre-service teacher and professional training of the physical education teacher in early childhood education: meanings of a teacher residency - Vilas Boas, Marcos; Ferraz, Osvaldo Luiz (Brazilian journal of physical education and sport, 2023)
This article presents the results of a research that aimed to investigate the meanings that pre-service teachers of a Physical Education degree course in the city of São Paulo attribute to the experience of a teacher residency in professional training. Ten students from the 5th and 6th semesters, who took the Physical Education courses in Early Childhood Education I and II, participated of this study. A focus group interview (n=5) was used for data collection. Categorical thematic content analysis was used as a reference for analyzing the internal structure of the categories and their relationships. Five categories and five subcategories emerged from data analysis. The results indicate that the experience of this teacher residency was significant in the professional training of the pre-service teachers, since they intertwined the lessons learned from university disciplines to the situations and problems experienced in the campus classes. Moreover, the data reveal the importance of building a professional knowledge base, which allows the pre-service teacher, in face of the demands that professional practice imposes, to mobilize knowledge for a contextualized action, allowing the construction and reconstruction of the practice for an action that is for coming.